An efficient data gathering algorithm for large-scale wireless sensor networks with mobile sinks. (2018) - Zhao, Jumin; Tang, Qingming; Li, Deng-ao; Zhu, Biaokai; Li, Yikun
Recently, wireless sensor networks with mobile sinks (mWSN) have attracted massive attention attributed to the benefits of mobility. The updating of routing, however, will generate a lot of control packets due to the movements of mobile sinks in mWSN, which will consume a lot of energy and reduce the life of network. This paper proposed a data gathering algorithm for large-scale mWSN. In the proposed algorithm, the entire network was divided into several gathering scopes . Each gathering scope locally updates the routing structure according to the path extension ratio which can effectively reduce the control packets generated by the updating of routing. To decrease the frequency of updating and the energy consumption of network, anchor nodes chains are adopted. Extensive simulation results show that the proposed algorithm can significantly reduce the control packets and prolong the lifetime of network when compared with other algorithms.